Factors Influencing the Decision of an Islamic Boarding School to Choose Face-to-Face Learning During Pandemic - Aziz, Abdul; Purwastuti, Lusila Andriani; Marzuqi, Muhammad Ali Baidlowi; Bahrudin, Aceng; Ariyunita, Noorrela (EDUKASIA, 2022)
This study highlights the factors influencing face-to-face learning decision-making by an Islamic boarding school during the pandemic. This qualitative descriptive-analytic study was conducted at MA Miftahunnajah, Sleman. Interviews, documentation, and observations were used to collect data. The research revealed that the following factors influenced face-to-face learning decisions: 1) internal conditions, such as boarding school security, student order, parental involvement, geographic location, and curriculum structure; 2) information availability; 3) external conditions, including community involvement and collaboration with other schools; 4) personality and skills of decision-makers. In addition, the Islamic boarding school's security was the most influential factor in all these factors, so facilitating schools with dormitories or boarding schools as places for students to live and study is a more appropriate solution than forcing online learning.